Protecting the Coast Over Time: Interview with Four Maine Coast Heritage Trust Staff Members - Pierson, Elizabeth; Arbuckle, Jane; Gabrielson, Jeremy; Ham, Betsy; Romano, Jeff (Maine Policy Review, 2023)
Since its founding in 1970, Maine Coast Heritage Trust—our only statewide land trust focused on the entire coast—has had an extraordinary impact on coastal protection. Working on hundreds of projects with partners from Kittery to Lubec, MCHT has helped conserve almost 180,000 acres and 335 islands. It holds more than 300 conservation easements and owns and stewards more than 155 public preserves. Protected sites include scenic islands and shorelines, working waterfronts, water-access sites, active farmlands, and community parks, trails, and greenspaces. In addition to its work on individual conservation projects, MCHT was instrumental in establishing the Land Trust Alliance, the nation’s leading land conservation advocacy group (1981); Land for Maine’s Future program (1987); and many Maine land trusts. My interview with four senior staff members took place in May 2023.